2008
DOI: 10.1038/nchembio.112
|View full text |Cite
|
Sign up to set email alerts
|

A sodium-mediated structural switch that controls the sensitivity of Kir channels to PtdIns(4,5)P2

Abstract: Inwardly rectifying potassium (Kir) channels are gated by the membrane phospholipid phosphatidylinositol-4,5-bisphosphate (PIP2). Among them, Kir3 channel gating requires additional molecules, such as the βγ subunits of G proteins or intracellular sodium. Using an interactive computational-experimental approach, we show that sodium sensitivity of Kir channels involves the side-chains of an aspartate and a histidine located across from each other in a critical loop in the cytosolic domain, as well as the backbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…‫ء‬ interacting with G␤␥ (Mahajan et al, 2013). The mutants constructed for the salt-bridge residue exchange experiment (Kir3.2 ‫ء‬ _S196R, Kir3.2 ‫ء‬ _R201E, and Kir3.2 ‫ء‬ _S196R_R201E) did not yield measurable current, which neither lent support nor refuted the salt-bridge hypothesis between phosphoSer-196 and Arg-201.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…‫ء‬ interacting with G␤␥ (Mahajan et al, 2013). The mutants constructed for the salt-bridge residue exchange experiment (Kir3.2 ‫ء‬ _S196R, Kir3.2 ‫ء‬ _R201E, and Kir3.2 ‫ء‬ _S196R_R201E) did not yield measurable current, which neither lent support nor refuted the salt-bridge hypothesis between phosphoSer-196 and Arg-201.…”
Section: Discussionmentioning
confidence: 65%
“…Homotetramers of Kir3.2 may exist in the substantia nigra pars compacta, where there does not appear to be expression of its usual heteromeric partner, Kir3.1 (Inanobe et al, 1999). Kir3.2 is readily activated by G␤␥ via Gi-coupled GPCRs (Logothetis et al, 1987;Hibino et al, 2010), whereas alternate pathways of control, such as channel inhibition via Gq-coupled GPCRs, are less well understood (Kobrinsky et al, 2000;Leaney et al, 2001;Brown et al, 2005;Hibino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kir-type K ϩ channels, the negative residues in the cytosolic region have been identified as playing a crucial role in Na ϩ -dependent activation (10,37). Results obtained by an interactive computational-experimental approach based on the crystal structure of the cytosolic domain of Kir3.1 suggest that the Na ϩ binding motif in Kir-type channels is DXRXXH (26). However, this sequence is not present in KtrB.…”
Section: Discussionmentioning
confidence: 98%
“…19 Interestingly, the same CD loop residues also play a critical role in regulating the function of different Kir channels by other modulators including the phosphoinositide PI(4,5)P 2 , [23][24][25] which is required for Kir channel activation, 8,23,[26][27][28] and intracellular sodium. [29][30][31][32] We have previously shown that in addition to Kir2.1, also other members of the Kir2 subfamily were also suppressed by cholesterol. 9 However, whereas the sensitivity of Kir2.1 and Kir2.2 to cholesterol was similar, Kir2.3 and Kir2.4 exhibited residues to the corresponding residues in Kir2.2.…”
Section: And Irena Levitanmentioning
confidence: 99%